Importance of customized (task oriented) software tools for biomedical applications - Khan, Haseeb A (Bioinformation, 2020)
Biomedical scientists and clinicians often require customized and user-friendly software tools due to the unavailability of specific software, complexity of existing software or high cost of commercial software. This editorial provides a short update on recently published task-oriented biomedical software tools. The novelty and applications of some customized software tools including CALCFISHER, CALCNTCP, CALCDOSE, and SCEW are also summarized in this editorial.